قياس وتحليل تفاعل عمل المضاعف والمعجل في الاقتصاد العراقي باستخدام نموذج المستخدم – المنتج الديناميكي - البيرماني صلاح مهدي (Journal of Economics and Administrative Sciences, 2008)
The individual average income is considered one of the most used criteria for the distinguishing between the developed and the developing countries, for this reason the efforts of economic development has been construed on increasing the average national income, the investment expenditures is considered one of the basic foundations for economic development operation which lead to the expanding the prodection power of the economy, and increasing the level of national income in an averages greaten than the primary expenditures due to the work and interaction between the multiplier and the accelerator. But the ability of the economic sectors in the generation of national income as a result of the primary expenditures is different from one section to the other according to the relationships for this section with the other sectors and in addition to the output/capital ratios. For this reason we must have knowledge about those sectors that have great ability to generate income, in order to provide and directed the big push of investments to these sectors. After analyzing the dynamic input - output, the best methods for the studying of the interaction between the multiplier and the acceleration for its ability to be calculator on the level of each sector and also on the level of national income. During considering and calculating the interaction between the multiplier and the calculator you the Iraqi economy 1982 was considered the best year in the achievement of the Iraqi economy. Because the changes in the final demand was amounted to one unit on the level of each factor, and realized income amounted to I.D. 53.74 on the level of the Iraqi national income in compansion with the years 1976 and 1988.